Yeast polysaccharide supplementation: impact on lactation, growth, immunity, and gut microbiota in Dezhou donkeys - Huang, Bingjian; Khan, Muhammad Zahoor; Chen, Yinghui; Liang, Huili; Kou, Xiyan; Wang, Xinrui; Ren, Wei; Wang, Changfa; Zhang, Zhenwei (Frontiers in Microbiology, 2023)
The Dezhou donkey, a prominent Chinese breed, is known for its remarkable size, rapid growth and resilience to tough feeding conditions, and disease resistance. These traits are crucial in meeting the growing demand for Ejiao and donkey meat. Yeast polysaccharide (YPS), a functional polysaccharide complex known for its immune-enhancing and growth-promoting properties in livestock and poultry, remains relatively understudied in donkeys. This study aimed to investigate the impact of YPS supplementation on lactating and growing Dezhou donkey jennies and foals. Twelve 45-day-old Dezhou donkey foals and their jennies, matched for body weight and age, were randomly allocated to two dietary groups: a control group receiving a basal diet and an experimental group receiving the basal diet supplemented with 10g/pen of YPS. The experiment was conducted over a 23-day period, during which donkey foals and lactating jennies were co-housed. The findings revealed that YPS supplementation had no adverse effects on milk production or composition in Dezhou donkey jennies but significantly increased feed intake. Additionally, YPS was associated with increased plasma glucose and creatinine concentrations in foals, while tending to decrease alkaline phosphatase, white blood cell count, red blood cell count, and hemoglobin levels (P<0.10).Immune indices demonstrated that YPS supplementation elevated the levels of immunoglobulin A (IgA) and immunoglobulin G in jennies (P<0.05) and increased complement component C4 concentrations in foals(P<0.05). Moreover, YPS positively influenced the fecal microbiome, This is a provisional file, not the final typeset article promoting the abundance of beneficial microorganisms such as Lactobacillus and Prevotella in donkey foals and Terriporobacter and Cellulosilyticum in jennies, all of which contribute to enhanced feed digestion. Additionally, YPS induced alterations in the plasma metabolome for both jennies and foals, with a predominant presence of lipids and lipid-like molecules. Notably, YPS increased the concentrations of specific lipid metabolites,including13,14-Dihydro PGF2a, 2-Isopropylmalic acid, 2,3-Dinor-TXB2, triterpenoids, taurocholic acid, and3b-allotetrahydrocortisol, all of which are associated with improved animal growth. In conclusion, this study suggests that dietary supplementation of YPS enhances feed intake, boosts immunity by increasing immunoglobulin levels, stimulates the growth-promoting gut microbiota(LactobacillusandPrevotella), and exerts no adverse effects on the metabolism of both Dezhou donkey jennies andfoals.